OP0087 TRENDS IN HIP FRACTURE INCIDENCE IN WOMEN AND MEN OVER 1980-2015 IN OLMSTED COUNTY, MINNESOTA, USA. (June 2019) - Bekele, Delamo; Kearns, Ann; Atkinson, Elizabeth; Amin, Shreyasee
Abstract : Background: Hip fracture incidence, which has been generally declining in North America, may have recently plateaued in women (Lewiecki, et al 2018). Objectives: We examined the trends in hip fracture incidence over 1980-2015, in both women and men, from Olmsted County, Minnesota, USA. Methods: Using the Rochester Epidemiology Project, a unique medical records linkage system that allows access to all (inpatient and outpatient) community medical records for Olmsted County residents, we identified all incident hip fractures among residents age ≥18 years between 1980-2015. Available medical records were reviewed by trained nurse abstractors to validate hip fractures identified and to determine their antecedent cause (pathological process [e.g., malignancy], severe trauma [e.g., motor vehicle accidents] and those due to no more than moderate trauma [by convention, equivalent to a fall from standing height or less]). Overall incidence rates were summarized separately for women and men, as well as by 5 year strata for different age groups (ages 18-39, 40-59, 60-79 and ≥ 80 yrs). Rates for women and men were each directly age-adjusted to the population distribution of US whites in 2010. Results: Between 1980-2015, we identified 2488 hip fractures in women (73%, median age 84 yrs) and 918 hip fractures in men (27%, median age 80 yrs), 97.4% of which were in whites. The majority of hip fractures were due to no more than moderate trauma (88% in women; 81% in men). The overall age-adjusted annual incidence of first hip fracture over 1980-2015 was 154 per 100, 000 person-years (p-y) for women and 98 per 100, 000 p-y for men. Hip fracture rates have decreased overall in women since 1980 (Table), however since 2005, there has been a trend for increasing hip fractures among women age 40-59 yrs and since 2010, a possible plateau vs. slight increase in hip fracture rate for women age ≥ 80 yrs. In men, there has been a general decrease in rates among those age 60-79 yrs and, at least since 2005, in men age ≥ 80 yrs, but there may be a trend for increasing hip fractures since 2010 in men age 40-59 (Table). Conclusion: There appears to be different trends in hip fracture rates for women and men and by age groups. The factors contributing to the observed recent increases in hip fracture rates among women and men ages 40-59 yrs warrant further attention. As suggested by others, there may be a recent plateau vs. slight increase in hip fracture rates in older women, which we noted in women age ≥ 80 yrs since 2010. The decrease in hip fractures in older men, particularly in those age ≥ 80 yrs, may reflect improved awareness in recent years of osteoporosis in men with initiation of treatment or better mitigation of risk factors, but warrants further review. Reference: [1] Lewiecki E.M., et al. Hip fracture trends in the United States, 2002 to 2015. Osteoporos Int29(3):717-722, 2018. Disclosure of Interests: None declared